Macroautophagy Regulation during HIV-1 Infection of CD4+ T Cells and Macrophages - Borel, Sophie; Espert, Lucile; Biard-Piechaczyk, Martine (Frontiers in Immunology, 2012)
Autophagy is an intracellular mechanism whereby pathogens, particularly viruses, are destroyed in autolysosomes after their entry into targets cells. Therefore, to survive and replicate in host cells, viruses have developed multiple strategies to either counteract or exploit this process. The aim of this review is to outline the known relationships between HIV-1 and autophagy in CD4+ T lymphocytes and macrophages, two main HIV-1 cell targets. The differential regulation of autophagy in these two cell types is highlighted and its potential consequences in terms of viral replication and physiopathology discussed.